Potencial of Rice Bran Extract as a Basic Ingridient in Candida albicans Culture Media - Rafika Rafika; Rahman Rahman; Ridho Pratama; Putri Sri Saqinah Sudirman; Mursalim Mursalim (Jurnal Media Analis Kesehatan, 2023)
Rice bran is a natural material that contains nutrients that serves as a fungal growth factor, can be used as an alternative media base for fungal growth. The aim of this research is to determine the potential of rice bran as an alternative medium for the growth of Candida albicans. The research design employed an experiment that compared the growth of Candida albicans on rice bran extract media and Sabouraud Dextrose Agar (SDA) media. The sample is rice bran powder obtained from rice mills and rice bran extract was made using a multi-stage pretreatment method. The rice bran extract was used to create Rice bran Agar (RBA) and Rice bran Liquid (RBC) media, while SDA dan (SDB) media were also prepared. The media were inoculated with Candida albicans, incubated, and observed for 5 days. Data analysis included the measurement of fungal colony diameter using One Way Anova and Candida albicans biomass using an independent t-test. The research findings indicate that the average diameter of fungal colonies on RBA extract media was 10.4 mm, whereas it was 12.3 mm on SDA media. The Anova and Post Hoc Tukey HSD results demonstrated significant daily differences in colony diameter on RBA media, indicating notable Candida albicans growth. Conversely, there was no significant difference in colony diameter on SDA media. The biomass average of Candida albicans on RBC media was 0.82 g, compared to 0.45 g on SDB media. The Mann-Whitney test (p < 0.05) indicated a significant contrast in the average dry weight of Candida albicans biomass, with RBC media being heavier than SDB media. The conclusion is RBA and RBC media have the ability to grow Candida albicans which can be used as an alternative to SDA and SDB media.